2012
DOI: 10.1007/s10047-012-0650-8
|View full text |Cite
|
Sign up to set email alerts
|

Numerical comparison of the closing dynamics of a new trileaflet and a bileaflet mechanical aortic heart valve

Abstract: The closing velocity of the leaflets of mechanical heart valves is excessively rapid and can cause the cavitation phenomenon. Cavitation bubbles collapse and produce high pressure which then damages red blood cells and platelets. The closure mechanism of the trileaflet valve uses the vortices in the aortic sinus to help close the leaflets, which differs from that of the monoleaflet or bileaflet mechanical heart valves which mainly depends on the reverse flow. We used the commercial software program Fluent to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…10 The TFUR design aims at reduced thrombogenicity (not requiring anticoagulation therapy) while maintaining the high durability of mechanical valves. 10,[15][16][17][18][19][20] The geometric orifice area (GOA) and its evolution over a pulse cycle is a frequently used metric for studying the kinematics of heart valves. [11][12][13][14] Although being valuable for a global analysis of the valve kinematics, this parameter has some limitations that are often overlooked: GOA is unable to capture asynchronous leaflet motion and does not provide any information on the out-of-plane velocity component of the leaflet motion.…”
mentioning
confidence: 99%
“…10 The TFUR design aims at reduced thrombogenicity (not requiring anticoagulation therapy) while maintaining the high durability of mechanical valves. 10,[15][16][17][18][19][20] The geometric orifice area (GOA) and its evolution over a pulse cycle is a frequently used metric for studying the kinematics of heart valves. [11][12][13][14] Although being valuable for a global analysis of the valve kinematics, this parameter has some limitations that are often overlooked: GOA is unable to capture asynchronous leaflet motion and does not provide any information on the out-of-plane velocity component of the leaflet motion.…”
mentioning
confidence: 99%
“…In terms of viscous model, simulations of BMHV involving FSI can basically be categorized as laminar model and direct numerical simulation (DNS). The former approach neglects turbulence and the mesh deformation is solved using the ALE approach provided by the CFD solver FLUENT in [ 7 9 , 23 , 26 , 27 ], which was adopted in the current study. The DNS approach adopts the fixed grid method with a much higher grid number in the order of 10 7 , and the simulations were conducted using in-house code [ 1 , 3 , 12 , 31 , 48 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Intermediate remeshing is necessary when a large deformation is involved such as rotating heart valve leaflets. For the numerical simulations of mechanical heart valves and heart ventricles, ANSYS FLUENT software is the most widely used CFD solver using ALE approach and the corresponding experimental validations have been conducted using Particle Image Velocimetry (PIV) [ 6 , 7 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Computational and in vitro studies indicated that this valve closes much slower than bi-leaflet valves and similar to the closing mode of a tissue valve (Fig. 1) [7,8]. Studies using micro-PIV were unable to identify any critical zones of excessive shear in the pivoting region, suggesting a lower thrombogenic potential compared to classical recessed hinge designs [9].…”
mentioning
confidence: 83%